A Corpus Study of Commissive Speech Acts Performed by USA Presidential Candidates - Gede Irwandika (ELLITE, 2021)
This study aims to investigate the commissive acts produced by the two USA presidential candidates in 2020 campaign. Campaign is selected as the source of media to gather data since the utterances tend to be more complete and not cut by mediator as if in a debate. The researcher employs a corpus analysis to study the commissive acts produced by USA presidential candidates. The researcher built his own corpus by transcribing the data from the speech of the candidates. There are total 9246 words built as the corpora of this study. The data were then calculated by using Antconc 3.5.8 software to look at the occurrences and class of commissive acts appeared. Further, the researcher also provided an in-depth description of the analysis to support the findings of the study. The study found out that there were more commissive acts performed by Donald Trump compared to Joe Bidden with 87 and 77 respectively. The speech of Donald Trump in his campaign also contains more classes of commissive acts compared to Joe Bidden’s campaign which are 4 classes and 3 classes respectively. It is expected that this study contributes to the board of knowledge in pragmatics area, corpus analysis, and specifically to commissive act production. Specifically, this study contributes to the tendency of politicians in performing commissive acts as a sign of commitment to their voters.